Measurement of dijet azimuthal decorrelations in pp collisions at √s = 7 TeV - Anduaga, Xabier Sebastián (2011)
Azimuthal decorrelations between the two central jets with the largest transverse momenta are sensitive to the dynamics of events with multiple jets. We present a measurement of the normalized differential cross section based on the full data set (Ldt = 36pb-1) acquired by the ATLAS detector during the 2010 √s = 7 TeV proton-proton run of the LHC. The measured distributions include jets with transverse momenta up to 1.3 TeV, probing perturbative QCD in a high-energy regime.